Physico-chemical composition and sensory acceptability of sweet orange (Citrus sinensis L. Osbeck) fruits degreened with some climacteric fruits - Odeyemi, Olubukola Motunrayo; Makinde, Eyitayo Adekunle; Ojetayo , Abiola Elizabeth (Journal of Postharvest Technology, 2019)
The practice of degreening sweet orange fruits was developed to promote colour development on the rind to make the fruits more attractive to consumers. This study was carried out to assess the efficacy of some climacteric fruits as a source of ethylene to degreen sweet orange fruits and to assess the sensory acceptability after degreening. Sweet orange fruits (Agege 1 variety budded on Cleopatra mandarin rootstock) were harvested at mature green ripe stage from an 8-year old organic citrus orchard at the Federal University of Agriculture, Abeokuta, Nigeria in the early season harvests of 2015 and 2016. Fruits of similar weight were stored in different plastic containers (9 litre capacity) at ambient condition (28-290C and 75-80% RH). Degreening was induced with climacteric fruits namely: Apple (Malus domestica), Avocado (Persea americana) and African bush mango (ABM) (Irvingia gabonesis) fruits while the un- induced sweet orange fruits served as control. Sweet orange fruits degreened with apple, avocado and ABM fruits had comparable pH, titratable acidity, total soluble solids, juice content and juice colour values. Vitamin C contents of sweet orange fruits degreened with apple fruits improved the quantity of vitamin C contents at 39.65 mg/100ml and 38.38 mg/100ml in 2015 and 2016 early harvests respectively with degreening and were significantly higher (p<0.05) than values obtained in other treatments. Rind color change from green to full yellow was earliest in sweet orange fruits degreened with apple fruits at 3 days after exposure in both years and had the overall best consumer’s acceptability in terms of appearance, taste and aroma. Use of apple fruits could be a source of ethylene to degreen sweet orange fruits on a small scale